2015
DOI: 10.1002/pam.21833
|View full text |Cite
|
Sign up to set email alerts
|

Waging War on Poverty: Poverty Trends Using a Historical Supplemental Poverty Measure

Abstract: Using data from the Consumer Expenditure Survey and the March Current Population Survey, we provide poverty estimates for 1967 to 2012 based on a historical Supplemental Poverty Measure (SPM). During this period, poverty, as officially measured, has stagnated. However, the official poverty measure (OPM) does not account for the effect of near-cash transfers on the financial resources available to families, an important omission since such transfers have become an increasingly important part of government anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 36 publications
7
124
0
Order By: Relevance
“…Therefore, the income supports and direct benefits provided by these government programs have cut family poverty almost in half, from an estimated 31% to approximately 16%. 29 …”
Section: What Work To Ameliorate the Effects Of Child Povertymentioning
confidence: 99%
“…Therefore, the income supports and direct benefits provided by these government programs have cut family poverty almost in half, from an estimated 31% to approximately 16%. 29 …”
Section: What Work To Ameliorate the Effects Of Child Povertymentioning
confidence: 99%
“…1-3 The poverty measure we use is based on the Census Bureau and Bureau of Labor Statistics' new Supplemental Poverty Measure, which is widely considered to be an improved measure of income poverty relative to official statistics because it takes into account government transfers such as the EITC and Food Stamps not counted in the official measure, geographic differences in cost of living, as well as costs such as medical expenses, child care, and commuting. 4 Families are classified as poor if their annual income (defined as post-tax cash income plus in-kind benefits, less expenditures for medical care, child care, or commuting) falls below a poverty line specific to New York City.…”
Section: Conceptualizing and Measuring Disadvantagementioning
confidence: 99%
“…In recent work, researchers have produced historical SPM estimates for the period 1967–2012, using data on incomes from the 1968–2013 Annual Social and Economic Supplement (ASEC) to the Current Population Survey (March CPS) and data on expenditures from the 1961, 1972/1973, and 1980–2012 Consumer Expenditure Survey (CE) (see Fox et al 2015). Those estimates showed that government policies have played a more important role in reducing poverty, particularly in recent years, than suggested by the OPM.…”
Section: Introductionmentioning
confidence: 99%
“…These thresholds are quasi-relative, in that the SPM methodology applies the same metric—the 30th to 36th percentile of expenditures on food, clothing, shelter, and utilities, plus 20 % more to cover other essentials—to define the poverty line over time. 2 For a discussion of trends in poverty using a quasi-relative measure, see Fox et al (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation